2019
DOI: 10.1101/804443
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep metagenomics examines the oral microbiome during dental caries, revealing novel taxa and co-occurrences with host molecules

Abstract: 45Dental caries is the most common chronic infectious disease globally. The microbial communities 46 associated with caries have mainly been examined using relatively low-resolution 16S rRNA gene 47 amplicon sequencing and/or using downstream analyses that are unsound for the compositional 48 nature of the data provided by sequencing. Additionally, the relationship between caries, oral 49 microbiome composition, and host immunological markers has not been explored. In this study, 50 the oral microbiome and a p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 99 publications
(122 reference statements)
1
10
0
Order By: Relevance
“…Although it has long been discussed whether functional pro les outperform taxonomic pro les for microbiome classi cation tasks [76], the predicted functional pro les from OSCC-associated individuals were reported similar despite the variation of the taxonomic pro les [15]. Besides, a recent shotgun metagenomic study [77] also supports our results by discriminating healthy controls from dental caries cohorts more effectively using pathways than taxa. In contrast to our ndings, another study with gut microbiome datasets [78] showed a worse performance from function-based searches compared to those using the taxa-based strategy.…”
Section: Discussionsupporting
confidence: 79%
“…Although it has long been discussed whether functional pro les outperform taxonomic pro les for microbiome classi cation tasks [76], the predicted functional pro les from OSCC-associated individuals were reported similar despite the variation of the taxonomic pro les [15]. Besides, a recent shotgun metagenomic study [77] also supports our results by discriminating healthy controls from dental caries cohorts more effectively using pathways than taxa. In contrast to our ndings, another study with gut microbiome datasets [78] showed a worse performance from function-based searches compared to those using the taxa-based strategy.…”
Section: Discussionsupporting
confidence: 79%
“…In another study of children with deep dentin caries disease, we found that bacterial community members belonging to the Rothia genus, specifically Rothia mucilaginosa, were enriched in saliva from healthy children compared to saliva from children with caries (15). From the same metagenomes, we also identified BGCs that were identical to those harbored by the complete genome sequence representing Rothia mucilaginosa ATCC 25296 (15). Based on this, we employed the oral Rothia mucilaginosa ATCC 25296 as a model species in this study.…”
Section: Resultsmentioning
confidence: 83%
“…Previously, our research team conducted a genome mining survey, targeting BGCs in 461 oral bacterial genomes, which identified a vast unexplored repertoire of ϳ5,000 putative BGCs (4). In another study of children with deep dentin caries disease, we found that bacterial community members belonging to the Rothia genus, specifically Rothia mucilaginosa, were enriched in saliva from healthy children compared to saliva from children with caries (15). From the same metagenomes, we also identified BGCs that were identical to those harbored by the complete genome sequence representing Rothia mucilaginosa ATCC 25296 (15).…”
Section: Resultsmentioning
confidence: 99%
“…Saccharibacteria (formerly TM7) have an ultrasmall cell size, reduced genomes, and are thought to be obligate epibionts, dependent on physically-associated host species (1)(2)(3). Common constituents of the oral microbiota, Saccharibacteria have been increasingly linked to inflammation and disease (4)(5)(6). Saccharibacteria contains at least 6 distinct clades (G1-G6) (7,8), however all currently available human-associated complete genomes and cultured isolates belong to clade G1, leaving clades G2-G6 quite poorly understood.…”
Section: Observationmentioning
confidence: 99%